2011
DOI: 10.1021/pr1012976
|View full text |Cite
|
Sign up to set email alerts
|

Specialisation of the Venom Gland Proteome in Predatory Cone Snails Reveals Functional Diversification of the Conotoxin Biosynthetic Pathway

Abstract: Conotoxins, venom peptides from marine cone snails, diversify rapidly as speciation occurs. It has been suggested that each species can synthesize between 1000 and 1900 different toxins with little to no interspecies overlap. Conotoxins exhibit an unprecedented degree of post-translational modifications, the most common one being the formation of disulfide bonds. Despite the great diversity of structurally complex peptides, little is known about the glandular proteins responsible for their biosynthesis and mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 71 publications
2
43
0
Order By: Relevance
“…We showed that all three enzymes, PDI, PPI B, and BiP, efficiently assist in the oxidative folding of ␣-GI and ␣-ImI. PDI represents one of the most abundant soluble proteins in the venom gland of several cone snail species (16,37) and has previously been shown to improve in vitro folding rates of conotoxin substrates (18). We confirm this finding and further demonstrate the ability of PDI to efficiently unfold disulfide bonds in conotoxins under reducing conditions.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We showed that all three enzymes, PDI, PPI B, and BiP, efficiently assist in the oxidative folding of ␣-GI and ␣-ImI. PDI represents one of the most abundant soluble proteins in the venom gland of several cone snail species (16,37) and has previously been shown to improve in vitro folding rates of conotoxin substrates (18). We confirm this finding and further demonstrate the ability of PDI to efficiently unfold disulfide bonds in conotoxins under reducing conditions.…”
Section: Discussionsupporting
confidence: 77%
“…8Bii), with the main PDI isoform migrating at ϳ90 kDa. In a previous study (16), immunoblotting of two-dimensional gels revealed the presence of larger molecular weight isoforms of PDI in the venom glands of C. victoriae and C. novaehollandiae. Whether the 90 kDa band represents a different PDI isoform remains to be determined because proteins excised from BN-PAGE can exhibit deviating migration patterns due to the presence of encasing BN gel matrices.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The milky appeareance is mainly due to the presence of secretory granules ( Fig. 4C) that appear similar to those found in the venom duct of another molluscivorous cone snail, C. victoriae (34). The volume of the injected venom seems to vary according to the size of the animal, and generally 10 -20 l were collected per milking, with six different individuals pooled for our proteomic analysis.…”
Section: Resultssupporting
confidence: 55%
“…Two other conopeptides have entered human clinical trials for the treatment of neuropathic pain (12) and others are in preclinical evaluation. Furthermore, numerous fundamental biological studies focused on understanding the maturation of the venom (13), the influence of environment or cone snail development stage on conopeptide expression (14–16) and the phylogenetic relationships between toxins (17,18) have been published.…”
Section: Introductionmentioning
confidence: 99%